Ethics Of Islamic Consumption Behavior on Discount Promotion and Flash Sale (Overview of Theoretical Economics of Umar bin AL-Khattab) - Siti Mudrikah; Rosida Dwi Ayuningtyas (Universitas Wahid Hasyim, 2021)
Consumption is something that inseparable from human life. It becomes an activity that needs special attention. There are many E-commerce sites use flash sale and discount models to attract consumers. However, here they must be able to determine consumption patterns cleverly. Allah has forbidden stingy nature but also forbids excess in consuming. Therefore, this paper will discuss a perspective of consumption ethics in Islam regarding flash sales and discounts in an all-digital era as it is today. This research will use the literature study method from various previous studies, books, and several related sources in obtaining data as research material. This paper will discuss the limitations in Islam in consuming certain goods during flash sales and discounts through Umar bin Khattab's economic fiqh study so that consumers do not only obey temporary desires, however, there is an ultimate goal in human life so that worldly desires can be managed by the teachings of the Quran and Hadith.Keywords: Flash Sale, Discounts , Islamic Consumption Ethics, Maslahah